Women Heroes Behind Martin Luther King’s Civil Disobedience As One Of Major Moments In American History - Sucipto Sucipto (BUANA GENDER : Jurnal Studi Gender dan Anak, 2021)
Women in America has long history and journey towards their independent and rights, especially black women or African-American women. Their struggle for justice and equality has faced many challenges and turmoils ever since its movement begun. One of the movements was The Civil Rights movements by the mid of 20th century. Martin Luther King, Jr. was an African-American who vocalized in initiating and fighting for Civil Rights from black people community. His dedication for liberty and equality without segregation and racism is acknowledged to American and also has been used for references for many scholars in different fields of study globally. This paper is qualitative descriptive which focuses on describing the Women Heroes and their contributions behind Martin Luther King, Jr’s journey to struggle for Civil Rights in America. The findings shows that there are at least three heroes; Rosa Louise McCauley a.k.a Rosa Parks, Constance Baker Motley, and Coretta Scott King who did not only show their courage but also bring huge impacts to legalize the Civil Rights Movement. Rosa Parks acted as symbol of civil rights movements supported by Montley as their legal supporter, and also Coreta who had given her many intellectual thoughts to King. Their dedications were undenialiable and became spirit for African-American rights up until now. This paper contributes to further readings about civil rights movement and its features, especially women heroes behind the movement.